Relação entre toxicidade de proteínas Vip3Aa e sua capacidade de ligação a receptores intestinais de lepidópteros-praga - Marucci, Suzana Cristina [UNESP]; Figueiredo, Camila Soares [UNESP]; Tezza, Renata Izabel Dozzi [UNESP]; Alves, Eliane Cristina da Cunha [UNESP]; Lemos, Manoel Victor Franco [UNESP]; Desidério, Janete Apparecida [UNESP] (FapUNIFESP (SciELO), 2015)
The objective of this work was to evaluate the toxicity of new Vip3Aa proteins and their binding capacity to brush-border membrane vesicles (BBMV) in the intestine of Spodoptera frugiperda, Anticarsia gemmatalis, and Heliothis virescens neonate larvae. The proteins expressed by the genes vip3Aa42 and vip3Aa43 showed toxicity to S. frugiperda (LC50 of 78.2 and 113 ng cm-2, respectively) and A. gemmatalis (LC50 of 239.2 and 57.5 ng cm-2, respectively), but they showed low toxicity to H. virescens (LC50>5,000 ng cm-2). BBMV binding assays showed that the proteins bind effectively to the receptors on vesicles of the evaluated species, but this binding capacity is only effective on the activation of toxicity to the evaluated populations of S. frugiperda and A. gemmatalis.
Relationship between toxicity of Vip3Aa proteins and their binding capacity to intestine receptors of lepidopteran pests
Keywords: Anticarsia gemmatalis; Cry proteins; Heliothis virescens; Management of resistance; Membrane vesicles; Spodoptera frugiperda